A SYSTEMATIC REVIEW OF HYBRID LEARNING IN HIGHER EDUCATION: IMPLEMENTATION STATUS, ADVANTAGES, CHALLENGES, AND FUTURE DIRECTIONS - Zhong, Yanhua; Rosli, Mohd Shafie (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
In the digital era, traditional higher education models face significant challenges in terms of flexibility and accessibility. Hybrid learning (HL) emerged as a transformative approach to address theses challenges, which involves onsite (i.e., in the classroom) and online (e.g., in different locations) students simultaneously under the instruction of the same teacher, has gained widespread global attention and application. Despite its benefits for teaching effectiveness and resource optimization, HL implementation faces significant obstacles. To gain an in-depth understanding of HL's current implementation status and promote its effective application, this study adopted the PRISMA protocol (literature screened April–June 2025; N = 115 articles) to conduct a systematic literature review on HL in higher education. We analyze HL’s definitions, implementation status, advantages (e.g., flexibility, accessibility, efficiency), challenges (e.g., technological barriers, pedagogical adaptation), and future directions. Findings reveal that while HL enhances educational access, its adoption requires addressing institutional readiness, faculty training, and equitable resource distribution. The study further identifies opportunities (e.g., AI integration, global collaboration) and proposes actionable recommendations for stakeholders (institutions, policymakers, ed-tech firms) to optimize HL practices. By synthesizing HL’s implementation landscape, this study aids educators and administrators in strategic decision-making and supports HL’s sustainable development in higher education.